From Market Making to Matchmaking: Does Bank Regulation Harm Market Liquidity?. (14th September 2022) - Saar, Gideon; Sun, Jian; Yang, Ron; Zhu, Haoxiang
Abstract: Postcrisis bank regulations raised market-making costs for bank-affiliated dealers. We show that this can, somewhat surprisingly, improve overall investor welfare and reduce average transaction costs despite the increased cost of immediacy. Bank dealers in OTC markets optimize between two parallel trading mechanisms: market making and matchmaking. Bank regulations that increase market-making costs change the market structure by intensifying competitive pressure from nonbank dealers and incentivizing bank dealers to shift their business activities toward matchmaking. Thus, postcrisis bank regulations have the (unintended) benefit of replacing costly bank balance sheets with a more efficient form of financial intermediation.